Electric barrier formation in kind of connected dip and hump of electric potential near ECR point - Barchuk, S.V.; Lapshin, V.I.; Maslov, V.I.; Onishchenko, I.N.; Tretyakov, V.N. (Вопросы атомной науки и техники, 2002)
The self-consistent formation, observed in experiments, of the solitary barrier for plasma electrons and ions has been analytically described.